Hypoxia Inducible Factor-1α Is a Regulator of Autophagy in Osteoarthritic Chondrocytes. (December 2021) - Lu, Junren; Peng, Yi; Zou, Jiapeng; Wang, Jiayi; Lu, Shunyi; Fu, Tengfei; Jiang, Libo; Zhang, Chi; Zhang, Jian
Objective: To investigate the relationship between hypoxia inducible factor-1α (HIF-1α) and the autophagic response in osteoarthritic chondrocytes (OA), under inflammatory insult as represented by in vitro OA model. Methods: Human chondrocyte cell line C28/I2 was cultured in both normoxic and hypoxic conditions and treated with interleukin-1β (IL1β) to emulate OA inflammatory insult in vitro . Cellular HIF-1α expression was silenced using siRNA transfection and cellular autophagic (P62/LC3II) response and OA chondrocyte damage (COL2A1/MMP13) related proteins were examined using western blotting. Cellular mitophagic (BNIP3/PINK1/Parkin) and apoptotic (Caspase/Cleaved Caspase 3) were also evaluated to assess mitophagy-mediated cell death due to HIF-1α silencing. Results: Chondrocyte basal autophagy levels were higher in a HIF-1α elevated environment and was more resistant to IL1β-induced inflammatory insult. Increase in autophagic proteins showed better chondrocyte repair, which resulted a lower level of reactive oxygen species production, and lesser damage to chondrocyte integrity. Silencing HIF-1α activates cellular PINK1/Parkin and BNIP3 mitophagic proteins, which leads to the activation of Caspase/Cleaved Caspase 3 apoptotic cascade. Conclusion: Our results show that chondrocyte autophagy is dependent on HIF-1α expression, showing the importance of HIF-1α in hypoxic chondrocyte function in OA. Dysregulation of HIF-1α expression results in the activation of mitophagy-mediated apoptosis.